Barriers and Challenges for Implementation of Janani Suraksha Yojna (JSY) from Gender Perspective in India (Bangladesh Journal of Medical Science, 2016)
Abstract not availableBangladesh Journal of Medical Science Vol.15(1) 2016 p.148-149